Environmental Chemistry Education Using Inquiry-Based Online Learning (Global Journal of Human-Social Science, 2024)
Due to the COVID-19 pandemic, educators worldwide are challenged to prepare instructional materials in a virtual environment to ensure learning and enable learners to take active and influential roles in addressing environmental challenges. This study used inquirybased online learning (IBOL) in teaching environmental chemistry to enhance the performance and attitude of graduate students in an online setting. The one-group pretest-posttest design was employed in the investigation. Mixed methods were utilized in data gathering and analysis. The designed learning modules were tried in MAED Science -Environmental Chemistry class (n=18) in the 1st semester, AY 2022-2023. The designed modules were assessed and rated "exceeds criteria" based on content, instructional design, organization, equity and accessibility, and presentation. Using IBOL has significantly improved the academic performance of students based on their pretest and posttest results.
Keywords: inquiry-based learning; environmental chemistry; online learning; one-group pretest-posttest design